Flavor Quality and Neuroprotective Effect of Blackberry Juice Fermented with Lactic Acid Bacteria - Xiayidan MAIMAITI, WU Han, LIU Xiaoli, Nurgul RAHMAN, DI Qingru, ZHOU Jianzhong, ZHONG Liang (Shipin Kexue, 2024)
In this study, blackberry juice was fermented with Lactobacillus plantarum P-S1016. The growth kinetic parameters of this strain were determined, and the organic acids and flavor substances of fermented blackberry juice were analyzed. Besides, its flavor quality was tested using an electronic tongue (E-tongue). The protective effect of fermented blackberry juice against corticosterone-induced injury in PC12 cells was investigated by measuring cell viability, reactive oxygen species (ROS) level, apoptosis rate, and mitochondrial membrane potential. The results showed that the growth kinetic model of L. plantarum P-S1016 had excellent goodness of fit with a determination coefficient (R2) of 0.943, and the bacterial concentration reached a maximum value of 9.40 (lg (CFU/mL)) at 29.28 h. The contents of lactic acid and succinic acid in fermented blackberry juice were 38.99 and 3.30 mg/mL, respectively, and the contents of esters, alcohols, acids, and other flavor components increased compared with those in fresh blackberry juice, with alcohols accounting for the highest proportion (33.28%) of the total, followed by alkanes (29.80%); the saltiness of blackberry juice was significantly reduced after fermentation. In addition, fermented blackberry juice at concentrations of 50 and 200 µg/mL significantly increased the survival rate of cells induced by corticosterone by (1.48 ± 0.07) and (1.60 ± 0.01) folds, reduced intracellular ROS levels, late apoptosis rate and the proportion of necrotic cells, and inhibited the decrease of mitochondrial membrane potential. In conclusion, blackberry juice fermented with L. plantarum P-S1016 has good taste and flavor quality and strong neuroprotective potential. It is expected to become a new functional natural plant-based beverage, which is important for improving the edible properties and functional value of blackberry fresh fruits.